A battery electrolyte and its preparation method and application

By using aluminum-based solid films to form an aluminum-based solid film on the positive and negative electrode surfaces of the lithium metal battery, the problems of structural instability and side reactions of high-nickel ternary positive electrode materials during the circulation process are solved, and the circulation performance and safety of the lithium metal battery are significantly improved.

CN113793985BActive Publication Date: 2025-04-22SUN YAT SEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110884049.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-03
Publication Date
2025-04-22
Estimated Expiration
2041-08-03

AI Technical Summary

Technical Problem

The structure of high-nickel ternary cathode materials is unstable during the circulation process, and are prone to cationic mixed discharge, phase transition and side reactions, resulting in poor battery circulation performance and safety hazards. How to prevent or slow down these structural damage is a challenge.

Method used

Aluminum alkoxide nanowires, fluorovinyl carbonate or vinyl carbonate are used as electrolyte additives to form a hard aluminum-based solid film with high ionic conductivity on the surfaces of the positive electrode and the negative electrode to suppress stress corrosion and phase change, and prevent the formation of dendrites.

Benefits of technology

It significantly improves the long cycle performance and rate performance of lithium metal batteries, enhances the structural stability of the positive electrode and the stability of the negative electrode, reduces the activity of side reactions and thermal side reactions, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003193319580000011
    Figure HDA0003193319580000011
  • Figure HDA0003193319580000012
    Figure HDA0003193319580000012
  • Figure HDA0003193319580000021
    Figure HDA0003193319580000021
Patent Text Reader

Abstract

The present invention discloses a battery electrolyte and a preparation method and application thereof, wherein the battery electrolyte contains alcohol aluminum nanowires and organic carbonate, wherein the organic carbonate includes at least one of fluoroethylene carbonate and vinylene carbonate. The present invention uses alcohol aluminum nanowires and fluoroethylene carbonate (or vinylene carbonate) as additives for lithium metal battery electrolytes, and can form a hard aluminum-based solid film with high ionic conductivity through the reaction of alcohol aluminum nanowires and fluoroethylene carbonate (or vinylene carbonate) on the surfaces of positive and negative electrodes, and the aluminum-based solid film can not only inhibit stress corrosion and structural decay of the positive electrode of the lithium metal battery, but also prevent the formation of dendrites on the lithium metal negative electrode, greatly improving the long cycle performance and rate performance of the lithium metal battery. The present invention develops a low-cost, high-efficiency, and environmentally friendly dual additive system, which is of great significance for the large-scale application of high-performance lithium metal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a battery electrolyte and a preparation method and application thereof. Background Art

[0002] High nickel ternary cathode materials (NCM) are known for their high specific capacity (>200mAh g -1 ), low cost, high energy density (>750Wh·kg -1 ) and other advantages, making it a strong candidate for commercial positive electrode materials for lithium metal batteries. However, the current high-nickel ternary positive electrode still has problems with poor cycle stability and serious safety hazards. The main reasons include: First, due to the similar radius of nickel ions and lithium ions, it is easy to cause cation mixing, making the structure of high-nickel ternary positive electrode materials unstable, and its layered structure is easily transformed into a spinel structure and then into a rock salt structure. These structural phase changes lead to an increase in the content of electrochemically inactive phases, which reduces the lithium ion diffusion rate and increases the electrochemical reaction impedance, resulting in poor battery cycle performance under high temperature and high rate conditions; secondly, the positive electrode particle / electrolyte interface side reactions are serious, including the electrolyte being Ni 4+ Oxidation / decomposition, oxygen evolution under high voltage, and dissolution of transition metal ions (TMs) by HF corrosion; finally, the secondary particles of high-nickel ternary cathode materials are prone to drastic volume changes and disintegration during the cycle, increasing the reaction area with the electrolyte, making the electrochemical and thermal side reactions with the electrolyte more serious, causing the consumption of active lithium ions, and the side reaction products hinder the mass transfer process, seriously affecting the cycle life and safety of high-nickel ternary cathode batteries. How to prevent or slow down the structural damage of high-nickel ternary cathodes at the particle and electrode levels is a big challenge.

[0003] In recent years, scientists have conducted a large number of studies dedicated to improving the structure and electrochemical performance of high-nickel ternary cathodes. The most commonly used methods include surface coating, adding electrolyte additives, and using gel polymer electrolytes. Among them, surface coating can effectively improve the stability of the particle / electrolyte interface. However, during the coating process, the cathode material is inevitably exposed to air and solvents for a long time, which can lead to the formation of an inactive passivation film on the surface of the cathode material. In addition, the coating is prone to detachment during cycling due to the volume change of the microspheres, resulting in further corrosion of the exposed fresh material surface by HF and side reactions, which has an adverse effect on the electrochemical performance of the cathode material. Liquid organic additives are a widely used cathode surface film-forming agent that can inhibit side reactions and transition metal dissolution at the electrode / electrolyte interface. However, the formed electrolyte film is relatively thick. Although it can protect the cathode surface, it will increase the resistance and reduce the diffusion rate of lithium ions at the interface. Gel polymer electrolytes are quasi-solid electrolytes, which have better flame retardancy than liquid electrolytes and better interfacial compatibility with electrodes, and can effectively reduce side reactions at the interface and slow down the dissolution rate of transition metals. However, there are still problems such as low ionic conductivity and poor mechanical stability. Therefore, it is particularly important to explore more effective comprehensive strategies to in-situ construct an electrochemically active coating on the cathode surface.

[0004] Nano-Al 2 O 3 is a widely used coating material that can significantly improve the electrochemical performance of cathode materials. Research shows that Al 2 O 3 coating can form an amorphous Li x AlO 1.5+0.5x (0 < x ≤ 1) thin film on the particle surface after cycling. This amorphous thin film exhibits excellent mechanical flexibility and stability due to its elastoplasticity, making it不易 to peel off during the lithiation / delithiation process, thus buffering the volume change during cycling and inhibiting the pulverization of secondary particles. At the same time, the strong Al-O bonds in the amorphous thin film bring excellent thermodynamic and kinetic stability, which helps to inhibit adverse structural evolution and TMs dissolution even at high voltages and high temperatures. In addition, the amorphous thin film has ionic conductivity, which can accelerate the transport of lithium ions at the interface.

[0005] Currently, atomic layer deposition and hydrothermal methods are usually used to coat a protective film on the surface of NCM electrodes. However, these methods require high temperatures and organic solvents, resulting in the formation of a passivation film on the surface of NCM. Moreover, the complex preparation process cannot guarantee the uniformity of the coating. Among these coating methods, some articles claim that during the cycling of NCM, the addition of electrolyte additives can in-situ generate a very uniform coating layer. Recently, some articles have confirmed that Al 2 O 3Inorganic particles can be used as a good electrolyte additive to deposit a protective film directly on the cathode surface. However, due to the size limitation of inorganic particles, this method cannot form a smooth and dense layer on the surface of a single NCM particle. In addition, the performance of lithium metal batteries is determined by the performance of the positive and negative electrodes, and inorganic additives also have an impact on the lithium negative electrode. The lithium negative electrode often forms dendrites and has serious side reactions with the organic electrolyte, resulting in reduced battery stability. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a battery electrolyte that can effectively inhibit the cracking and phase change of the positive electrode of a lithium metal battery and prevent the formation of dendrites on the lithium metal negative electrode.

[0007] At the same time, the present invention also provides a method for preparing the battery electrolyte, an electrolyte additive and application thereof.

[0008] Specifically, the present invention adopts the following technical solutions:

[0009] A first aspect of the present invention is to provide a battery electrolyte comprising aluminum alkoxide nanowires and an organic carbonate, wherein the organic carbonate comprises at least one of fluoroethylene carbonate (FEC) and vinylene carbonate (VC).

[0010] The inventors discovered that alcohol aluminum nanowires can react with fluoroethylene carbonate (FEC) or vinylene carbonate (VC). After adding them together to the electrolyte, a hard aluminum-based solid film with high ionic conductivity is formed on the surface of the positive and negative electrodes. This aluminum-based solid film can not only inhibit the stress corrosion and phase change of the positive electrode of the lithium metal battery, but also prevent the formation of dendrites on the lithium metal negative electrode, greatly improving the long cycle performance and rate performance of the lithium metal battery.

[0011] In some embodiments of the present invention, the aluminum alkoxide nanowires include aluminum ethoxide nanowires.

[0012] In some embodiments of the present invention, the diameter of the aluminum ethoxide nanowires is 20 nm to 200 nm.

[0013] In some embodiments of the present invention, ethanol aluminum nanowires are obtained by reacting AlLi alloy with ethanol.

[0014] In some embodiments of the present invention, the method for preparing the ethanol aluminum nanowires comprises the following steps: immersing the AlLi alloy in ethanol and allowing it to stand to obtain the ethanol aluminum nanowires. Preferably, the amount of ethanol used is at least enough to immerse the AlLi alloy, and can be adjusted according to actual needs. Preferably, the standing time is 20 to 60 hours, preferably 25 to 40 hours. Preferably, the standing temperature is 40 to 70°C, preferably 50 to 65°C.

[0015] In some embodiments of the present invention, the ratio of the aluminum alkoxide nanowire to the organic carbonate is 1 mg: 5-20 μL, preferably 1 mg: 10-20 μL.

[0016] In some embodiments of the present invention, the mass concentration of the aluminum alkoxide nanowire in the battery electrolyte is 0.1% - 1%, preferably 0.3% - 0.5%.

[0017] In some embodiments of the present invention, the battery electrolyte further includes a lithium salt and a solvent. The lithium salt and the solvent can adopt the common lithium metal battery electrolytes in the art. For example, the lithium salt can adopt LiPF 6 、LiBF 4 、LiClO 4 、LiAsF 6 at least one of them, and the solvent can adopt at least one of ethylene carbonate (EC) and diethyl carbonate (DEC). The concentration of the lithium salt can be set as needed, for example, 0.5 - 2 M.

[0018] The second aspect of the present invention is to provide a preparation method of the battery electrolyte, including the following steps: dissolving the aluminum alkoxide nanowire, the organic carbonate and the lithium salt in the solvent to obtain the battery electrolyte.

[0019] The third aspect of the present invention is to provide a lithium metal battery, including a positive electrode, the above battery electrolyte and a negative electrode.

[0020] In some embodiments of the present invention, the active material of the positive electrode includes (high-nickel) ternary positive electrode material LiNi 1-x-y Co x Mn y O 2 (NCM, 0 < x < 1, 0 < y < 1, preferably 0.1 ≤ x < 0.3, 0.1 ≤ y < 0.3, preferably Li[Ni 0.6 Co 0.2 Mn 0.2 O 2 )、lithium iron phosphate, lithium cobaltate, lithium manganate, lithium nickel cobalt aluminate at least one of them.

[0021] In some embodiments of the present invention, the loading amount of the active material in the positive electrode is 0.5 - 30 mg·cm -2 .

[0022] In some embodiments of the present invention, the negative electrode includes lithium metal.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention uses alcohol aluminum nanowires and fluoroethylene carbonate (or vinylene carbonate) as additives for lithium metal battery electrolytes, and can form a hard aluminum-based solid film with high ionic conductivity through the reaction of alcohol aluminum nanowires and fluoroethylene carbonate (or vinylene carbonate) on the surfaces of the positive and negative electrodes. The aluminum-based solid film can not only inhibit stress corrosion and structural decay of the positive electrode of the lithium metal battery, but also prevent the formation of dendrites on the lithium metal negative electrode, greatly improving the long cycle performance and rate performance of the lithium metal battery. The present invention develops a low-cost, high-efficiency, and environmentally friendly dual additive system, which is of great significance for the large-scale application of high-performance lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Al(EtO) prepared in Example 1 3 SEM images of nanowires (a) and commercial aluminum ethoxide (b).

[0026] Figure 2 The test results of the cycle performance of the lithium metal batteries of Example 1 and Comparative Example 1 are shown;

[0027] Figure 3 Schematic diagram of the lithium metal battery of Example 1(b) and Comparative Example 1(a);

[0028] Figure 4 SEM images of the lithium metal anode after cycling in the original electrolyte BE (a) and the modified electrolyte AFE (b), and SEM images of the NCM cathode after cycling in the original electrolyte BE (c) and the modified electrolyte AFE (d);

[0029] Figure 5 The cycle test results of the lithium metal batteries of Example 2 and Comparative Example 2 at 0.5C are shown;

[0030] Figure 6 The Cu||Li batteries of Example 1 and Comparative Examples 1, 3, and 4 were tested at a current of 0.5 mA·cm -2 , deposition amount is 1 mAh·cm -2 The coulombic efficiency under . DETAILED DESCRIPTION

[0031] The technical scheme of the present invention is further described below in conjunction with specific examples. The raw materials used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources; the processes used, unless otherwise specified, all adopt conventional processes in the art.

[0032] Example 1

[0033] Raw materials: Lithium rods (99.9%) and aluminum powder (99.5%) were purchased from Aladdin; ethanol (pure, anhydrous, ≥99.8%) and polyvinylidene fluoride (PVDF) were purchased from Sigma-Aldrich; Li[Ni 0.6 Co 0.2 Mn 0.2 ]O 2 The (NCM622) electrode was provided by Dongguan Kelude Experimental Equipment Technology Co., Ltd.; the original electrolyte (LB-008, 1M LiPF 6 in EC / DEC) was purchased from Suzhou Qianmin Chemical Reagent Co., Ltd.

[0034] (1) Preparation of aluminum ethoxide [Al(EtO) 3 Nanowires

[0035] Ethanol aluminum nanowires can be prepared by referring to the prior art [Lei, D. et al. Transformation of bulk alloys to oxide nanowires. Science. 355: 267-271 (2017)].

[0036] Specifically, lithium rods and aluminum powder are first used as materials for synthesizing AlLi alloy. About 0.085g Li and 0.3g Al (atomic ratio Li:Al = 1:1, 10% excess Li) are added to a graphite crucible lined with graphite paper. After heating at 800°C for 30 minutes, the graphite crucible is taken out of the muffle furnace and the graphite plunger is immediately pressed down to obtain AlLi alloy. 0.115g of the synthesized AlLi alloy is taken and placed in 20mL of anhydrous ethanol and placed at 60°C without stirring for 30 hours. A uniform Al(EtO) is obtained through a chemical desalination process. 3 Nanowires.

[0037] (2) The synthesized Al(EtO) 3 0.005 g of nanowires and 50 μL of fluoroethylene carbonate (FEC) were added to 1 ml of the original electrolyte LB-008 [Al(EtO) 3 The mass concentration of nanowires is 0.4%] and ultrasonic treatment is performed for 3 h to obtain a modified electrolyte, which is marked as AFE.

[0038] (3) Using NCM622 as the positive electrode {where the active material Li[Ni 0.6 Co 0.2 Mn 0.2 ]O 2 The loading capacity is 21.6 mg cm -2 , the proportion of active material is 96.5%}, Al foil is used as the current collector, lithium sheet is used as the negative electrode, the amount of modified electrolyte AFE is controlled at 60μL, and a button-type lithium metal battery is assembled.

[0039] To better understand the deposition behavior of Li metal anode and NCM cathode in electrolyte, Cu||Li cells were simultaneously assembled.

[0040] Example 2

[0041] The difference between this embodiment and embodiment 1 is that the positive electrode is replaced with a lithium iron phosphate electrode, wherein the loading amount of the active material lithium iron phosphate in the lithium iron phosphate electrode is 1.16 mg·cm -2 ; The amount of modified electrolyte AFE used to assemble the lithium metal battery is 30μL.

[0042] The other operations are the same as those in Example 1.

[0043] Comparative Example 1

[0044] The difference between this comparative example and Example 1 is that no Al(EtO) is added to the original electrolyte. 3 Nanowires and fluoroethylene carbonate. That is, the electrolyte of the lithium metal battery assembled in this comparative example is the original electrolyte LB-008 (marked as BE). Other operations are the same as those in Example 1.

[0045] Comparative Example 2

[0046] The difference between this comparative example and Example 2 is that no Al(EtO) is added to the original electrolyte. 3 Nanowires and fluoroethylene carbonate. That is, the electrolyte of the lithium metal battery assembled in this comparative example is the original electrolyte LB-008 (BE). Other operations are the same as those in Example 2.

[0047] Comparative Example 3

[0048] The difference between this comparative example and Example 1 is that only the same amount of fluoroethylene carbonate (FEC) is added to the original electrolyte, and Al(EtO) is not added. 3 The other operations are the same as those in Example 1.

[0049] Comparative Example 4

[0050] The difference between this comparative example and Example 1 is that only the same amount of Al(EtO) is added to the original electrolyte. 3 Nanowires were prepared without adding fluoroethylene carbonate (FEC). Other operations were the same as those in Example 1.

[0051] Structural characterization and performance testing:

[0052] (1) Al(EtO) prepared in Example 1 3 The microscopic morphology of nanowires is Figure 1As shown in the figure, Al(EtO) 3 The nanowires have a uniform nanofiber structure with a diameter of 20 to 200 nm. In contrast, the microscopic morphology of commercial aluminum ethanol was observed at the same time, and it was found that commercial aluminum ethanol was in a blocky shape, which would prevent it from being evenly distributed in the electrolyte, unable to effectively react with FEC, and unable to effectively and evenly protect the electrode.

[0053] (2) The lithium metal battery of Example 1 was activated for 3 cycles at 3.0-4.3 V and 0.1 C, and then multiple cycles were performed at 0.5 C. The cycle performance of the lithium metal battery of Example 1 was obtained as follows: Figure 2 As shown. For comparison, the lithium metal battery of Comparative Example 1 was treated in the same manner.

[0054] according to Figure 2 It can be seen that the initial discharge capacity of the lithium metal battery of Example 1 after three cycles of activation at 0.1C is 157.7 mAh·g -1 Even after 200 cycles at 0.5C rate, the reversible capacity is still 114.8 mAh g -1 In contrast, after 35 cycles of charge and discharge at a rate of 0.5C, the discharge capacity of the lithium metal battery in Comparative Example 1 rapidly increased from 137.7 mAh·g -1 Down to 10.7 mAh g -1 , long-term cycle performance is reduced.

[0055] The schematic diagram of the lithium metal battery of Example 1 and Comparative Example 1 is as follows Figure 3 In Example 1, Al(EtO) 3 Nanowires can react with FEC in the electrolyte to form a strong and stable film (CEI and SEI) on the surface of the positive and negative electrodes, preventing the structural evolution of NCM and the growth of lithium dendrites in long cycles. In the case of comparative example 1 without electrolyte additives, a large number of cracks appeared in the NCM, and obvious lithium dendrites were produced on the negative electrode side. Therefore, the lithium metal battery of Example 1 has such excellent long-term cycle performance, and the reason is that the formation of a dense CEI film prevents the structural evolution of NCM and the corrosion of the electrolyte in long cycles. The highly stable structure of the modified NCM battery significantly improves the cycle stability of the modified battery.

[0056] (3) The Cu||Li batteries of Example 1 and Comparative Example 1 were heated at 0.5 mA·cm -2 When operated at a fixed current density, the specific area capacity is limited to 3 mAh cm -2 , to obtain optical images. SEM images of the positive and negative electrodes are shown in Figure 4 shown. Figure 4a shows that in the original electrolyte BE, the lithium metal deposited on Cu has a typical dendritic morphology; while in the modified electrolyte AFE ( Figure 4 In b), due to the formation of a stable and highly ionic conductive SEI, uniform lithium deposition is achieved without the generation of obvious dendrites.

[0057] The morphological changes of the NCM positive electrode after 100 cycles at a current density of 0.5C were observed by SEM. It can be seen that the NCM particles circulating in the original electrolyte BE showed obvious cracking ( Figure 4 c), the cracks in NCM directly lead to the pulverization of the basic microcrystals, which will produce more fresh active sites to interact with the electrolyte, resulting in structural and interfacial instability, as well as HF corrosion, leading to the dissolution of transition metals from the active materials, and ultimately causing a sharp drop in the capacity of the original NCM material. However, the NCM particles circulating in the AFE battery still have a dense film without cracks ( Figure 4 d). This indicates that the NCM cathode forms a strong and Al-rich CEI in the modified electrolyte AFE, which inhibits the cracking of NCM particles. This highly stable structure of the electrode can well explain its excellent electrochemical performance.

[0058] (4) The cycle test results of the lithium metal batteries of Example 2 and Comparative Example 2 at 2.5-4.2V and 0.5C are as follows Figure 5 As shown. Figure 5 It can be seen that Al(EtO) 3 Nanowires and FEC can also have a good stability improvement effect on the stability of lithium metal batteries with lithium iron phosphate pole pieces as positive electrodes.

[0059] (5) The Cu||Li batteries of Example 1 and Comparative Examples 1, 3, and 4 were tested at a current of 0.5 mA·cm -2 , deposition amount is 1 mAh·cm -2 The Coulomb efficiency under Figure 6 shown. Figure 6 It is reflected that the coulombic efficiency of Example 1 using the modified electrolyte AFE is close to 100%, and there is almost no change after 100 cycles; while the original electrolyte BE is used in Comparative Example 1, and its initial coulombic efficiency is lower than that of Example 1, below 87.5%, and with the increase of the number of cycles, the coulombic efficiency gradually decreases, and completely drops to 0 after 100 cycles; while FEC is added to the original electrolyte in Comparative Example 3, although its initial coulombic efficiency is improved compared with that of Comparative Example 1, its coulombic efficiency is very unstable after 30 cycles, and fluctuates greatly, and the coulombic efficiency drops to less than 50% after 100 cycles; Al(EtO) is added to the original electrolyte in Comparative Example 4 3The initial coulombic efficiency of the nanowires did not change significantly compared with that of comparative example 1, and the stability was good within 60 cycles. However, the coulombic efficiency dropped significantly after 60 cycles, and the long-term stability was poor.

[0060] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A battery electrolyte, characterized in that: The battery electrolyte is composed of alkoxide aluminum nanowires, organic carbonate, lithium salt, and solvent; the organic carbonate includes at least one of fluoroethylene carbonate and vinylene carbonate; The lithium salt includes at least one of LiPF6, LiBF4, LiClO4, and LiAsF6; The solvent includes at least one of ethylene carbonate and diethyl carbonate; The alcohol aluminum nanowires are ethanol aluminum nanowires; The diameter of the ethanol aluminum nanowires is 20 to 200 nm; The ratio of the alcohol aluminum nanowires to the organic carbonate is 1 mg: 5-20 μL.

2. The battery electrolyte according to claim 1, characterized in that: The ratio of the alcohol aluminum nanowires to the organic carbonate is 1 mg: 10-20 μL.

3. The battery electrolyte according to any one of claims 1 to 2, characterized in that: The mass concentration of the alcohol aluminum nanowires in the battery electrolyte is 0.1% to 1%.

4. The battery electrolyte according to claim 3, characterized in that: The mass concentration of the alcohol aluminum nanowires in the battery electrolyte is 0.3% to 0.5%.

5. The method for preparing the battery electrolyte according to claim 1, characterized in that: The method comprises the following steps: dissolving alcohol aluminum nanowires, organic carbonate and lithium salt in a solvent to obtain a battery electrolyte.

6. A lithium metal battery, characterized in that: Comprising a positive electrode, the battery electrolyte according to any one of claims 1 to 4 and a negative electrode; The active material of the positive electrode includes LiNi 1−x−y Co x Mn y O2, where 0 < x < 1, 0 < y < 1, at least one of lithium iron phosphate, lithium cobaltate, lithium manganate, and lithium nickel cobalt aluminate; the negative electrode is lithium metal.

7. The lithium metal battery according to claim 6, characterized in that: The loading amount of the active material in the positive electrode is 0.5 to 30 mg cm -2 .

Citation Information

Patent Citations

  • High voltage lithium-ion battery electrolyte and lithium-ion battery

    CN103633369A

  • High-voltage LiNixCoyMnzM(1-x-y-z)O2 cathode material, preparation method thereof, cathode and battery

    CN105336941A

  • Preparation method for improving high temperature cycling performance of lithium manganite by doping Al3&lt;+&gt; and F&lt;-&gt;

    CN108258304A

  • Lithium ion secondary battery and electrolyte thereof

    CN109004277A